2020
DOI: 10.1074/jbc.ra120.013547
|View full text |Cite
|
Sign up to set email alerts
|

Lysines in the lyase active site of DNA polymerase β destabilize nonspecific DNA binding, facilitating searching and DNA gap recognition

Abstract: DNA polymerase (pol) b catalyzes two reactions at DNA gaps generated during base excision repair; gap-filling DNA synthesis and lyase-dependent 5' end deoxyribose phosphate removal. The lyase domain of pol β has been proposed to function in DNA gap recognition and to facilitate DNA scanning during substrate search. However, the mechanisms and molecular interactions used by pol b for substrate search and recognition are not clear. To provide insight into this process, a comparison was made of the DNA bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…During this analysis, the formation of several complexes with different mobility in the gel was recorded. Of note, the formation of several complexes with different gel mobility in the EMSA has also been reported earlier [ 48 , 49 , 50 ]. It is possible that Polβ forms complexes with DNA in some fixed intermediate states between the well-known open and closed conformations, and these intermediate states possess different electrophoretic mobility.…”
Section: Resultssupporting
confidence: 78%
“…During this analysis, the formation of several complexes with different mobility in the gel was recorded. Of note, the formation of several complexes with different gel mobility in the EMSA has also been reported earlier [ 48 , 49 , 50 ]. It is possible that Polβ forms complexes with DNA in some fixed intermediate states between the well-known open and closed conformations, and these intermediate states possess different electrophoretic mobility.…”
Section: Resultssupporting
confidence: 78%
“…Also, the phosphorylation might cause changes in the subcellular location of Tcpolβ, since it has been reported that in hydrogen peroxide treated epimastigote cells, Tcpolβ appears in new additional focus outside of the kDNA as compared to untreated cells [18]. It has been recently shown that mammalian DNA polymerase β can perform a processive search (DNA scanning) looking for DNA damage using its lyase domain [29,30]. This indicates that the dRP lyase domain of DNA polymerase β can non-specifically interact with DNA during the scanning process.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that three lysines in the lyase active site of Pol β facilitate the search for the 5′-flap substrate on the dsDNA and destabilize non-specific DNA binding. Mutating these three lysine residues to alanines in the lyase active site of Pol β (Lys 35, Lys 68, and Lys 72), increased the binding affinity of Pol β for nonspecific DNA, indicating a role of the 5′dRP lyase in the specificity of lesion recognition (Howard et al, 2020). A tumor-associated variant in the N-terminal 8 kDa domain of Pol β retains polymerase activity but is dRP lyase deficient (Dalal et al, 2008).…”
Section: -Drp Lyase Activitymentioning
confidence: 99%